Supramolecular self-assembly production of porous carbon nitride nanosheets with excellent photocatalytic activity by a melamine derivative as doping molecule. (January 2020) - Tang, Dan; Chen, Yefeng; Yin, Mengyun; Yang, Qin; Zhou, Yafen; Zhou, Limei
Abstract: Since doping has a good effect on improving the photocatalytic performance of carbon nitride (CN), the doping scheme has been extensively studied. In this work, a melamine derivative (2, 4-diamino-6-phenoxy-[1, 3, 5]-triazine, MA-phO) was synthesized and used as a new doping molecule to prepare the modified-CN materials by a facile supramolecular self-assembly method with melamine (MA) and cyanuric acid (CA). The "growth stoppers" effect caused by the doping molecule MA-phO in the supramolecular complex made the modified-CN materials more favorable for forming nanostructure and increasing the specific surface areas. The decomposition of phenyl group allowed C atoms to be incorporated into the CN skeleton which facilitated the separation of photogenerated h + /e − pairs. What's more, the addition of MA-phO could regulate the energy band structure of modified-CN materials. It has been found that the amount of doping molecule affected the photocatalytic performance of photocatalyst. Especially when the doping amount reached 0.5%, the prepared sample had the best photocatalytic activity for the organic pollutants. Significantly, design and synthesis of new melamine derivatives as doping molecules and pretreatment by using supramolecular self-assembly strategy may provide a facile approach for the preparation of tunable morphology, energy band structure and heteroatom-doped g-C3 N4 . Graphical abstract: Image 1